MEMBANGUN KEUNGGULAN KOMPETITIF CPO MELALUI SUPPLY CHAIN MANAGEMENT: STUDI KASUS DI PT. EKA DURA INDONESIA, ASTRA AGRO LESTARI, RIAU - Setiadi Djohar; Hendri Tanjung; Eko Ruddy Cahyadi (School of Business, Bogor Agricultural University (SB-IPB), 2004)
Todays, Supply Chain Management (SCM) becomes one icon of strategic factors to achieve a competitive advantage. This is a SCM case study in agroindustry especially crude palm oil (CPO) at PT. Eka Dura Indonesia (PT EDI), Astra Agro Lestari, Riau. The objectives of study is mapping of SCM problems of PT EDI, especially about value advantage and productivity advantage. Beside that, the objectives is building a SCM simulation model as strategic tool for developing strategy to achieve a competitive advantage. A system approach and modeling is used to analyze SCM problems. This study is successfully to build SCM Model that consist of SCM Strategic Model and SCM Tactic Model. SCM Model is used for simulating some scenarios about site management, supply schedulling, and tank management to CPO forecasting. From this model, the study also develops strategy chain for SCM to achieve a competitive advantage